The Prognosis of Maintenance Hemodialysis Patients With Various Types of Vascular Access in Hemodialysis Centers in Wuhan: A Retrospective Cohort Study - Li Cheng; Yonglong Min; Can Tu; Sheng Wan; Qianshen Zhu; Jing Chen; Wenhui Qiu; Nan Jiang; Hongbo Li (International Journal of Nephrology)
Conclusions: Among MHD patients with different vascular access types who were treated in Wuhan from 2017 to 2023, the numbers of AVF, AVG, and TCC patients increased with increasing overall number of MHD patients, whereas the number of NCC patients decreased. The overall condition and survival time of AVF patients were significantly better than those of MHD patients with other vascular access types, and the risk of death was lower.